UIN, IAIN, STAIN: Perkembangan Epistemologi dan Institusi Perguruan Tinggi Islam Indonesia - Mutimmatuz Zahro; M. Nurul Humaidi (Civiliza Publishing, Indonesia., 2026)
This study examines the institutional and epistemological development of three types of State Islamic Religious Universities (PTKIN) in Indonesia, namely State Islamic Religious Colleges (STAIN), State Islamic Religious Institutes (IAIN), and State Islamic Universities (UIN). Using the library research method with a qualitative approach, this study examines the institutional transformation from STAIN to IAIN and then UIN as part of the dynamics of modernization of Islamic education. Epistemologically, the change in institutional status is not merely an expansion of the structure, but reflects a paradigmatic shift from the Islamization of a single discipline to the integration-interconnection of science. The case study at UIN Maulana Malik Ibrahim Malang shows significant growth: from 28 study programs with 9,200 students in 2010 to 63 study programs with 24,750 students in 2024. The findings of the study illustrate that the conversion to UIN encourages a real epistemic expansion, despite being faced with the challenge of Islamic scientific identity in the midst of the expansion of general science. This research contributes by offering an epistemological-institutional comparative analysis framework that has not been widely developed in the Indonesian Islamic education literature.